Senate, Political Representation and Control: Essential Factors in Modern State Democracy - Gonzales Ojeda, Magdiel (2021)
The essence of the democratic system. requires Parliament to sufficiently important to exercise a real counterweight to the executive organ of the Government; Itis a political power which finds its immediate and direct   origin and its limitation in the Constitution; this power function we would say, of greater importance because the Parliament, in the modern state is the supreme organ of the State whose conformation expression of the will of the nation is assumed and exercised control function as immediate president and representative. The legislative branch is the supreme organ of the State, collegiate, pluralist, that is, that the people in it have different ideologies or belong to different political parties, whose essential functions are linked to the political control of the state, the development of law and the obligation to preserve the life of the state, taking care of the implementation of key state functions and respect for fundamental rights. lt may be composed of one or two legislative chambers. Parliament building in town participates actively in compliance with the principle of popular sovereignty and does so through political representation; thus with the above elements, the participation of all citizens of the state, political representation and supervision or control will develop the legislative branch in Peru.